Gender issues in Kaleckian distribution and growth models: On the macroeconomics of the gender wage gap - Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2020)
We introduce a gender wage gap into basic one-good textbook versions of the neo-Kaleckian distribution and growth model and examine the effects of improving gender wage equality on income distribution, aggregate demand, capital accumulation and productivity growth. For the closed economy model, reducing the gender wage gap has no effect on the profit share, and a gender equality-led regime requires the propensity to save out of female wages to fall short of the propensity to save out of male wages. For the open economy model this condition is modified by the effects of improved gender wage equality on exports and - through changes of the profit share - on domestic demand. Finally for the open economy with productivity growth we find an unambiguously expansionary effect of narrowing the gender wage gap on long-run equilibrium capital accumulation and productivity growth if the demand growth regime is gender equality-led. A gender equality-burdened demand growth regime, however, may generate different long-run effects of improving gender wage equality on capital accumulation and productivity growth: expansionary, intermediate or contractionary.
Keywords: E11; E21; E22; O40; O41; 330; gender wage gap; distribution; growth; Kaleckian model